2019
DOI: 10.1002/dac.3904
|View full text |Cite
|
Sign up to set email alerts
|

Efficient privacy‐preserving authentication scheme for roaming consumer in global mobility networks

Abstract: The advancements in wireless technologies have paved the way for offering seamless services to mobile consumers in global mobility networks (GLOMONETs). Nonetheless, since in these networks, the communication channels are open and public, devising proper measures to protect the security and privacy of exchanging messages is critical. Moreover, because of the energy and computational power limitations of the mobile devices, a security mechanism should put the least possible burden on these devices. To do so, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In recent years, many roaming authentication protocols [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][30][31][32][33][34][35][36] have been proposed to achieve secure information acquisition for mobile users with smart card in the ubiquitous network. In 2004, a roaming authentication protocol for the ubiquitous network was proposed by Zhu and Ma [5], which aims to preserve the privacy of mobile users.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, many roaming authentication protocols [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][30][31][32][33][34][35][36] have been proposed to achieve secure information acquisition for mobile users with smart card in the ubiquitous network. In 2004, a roaming authentication protocol for the ubiquitous network was proposed by Zhu and Ma [5], which aims to preserve the privacy of mobile users.…”
Section: Related Workmentioning
confidence: 99%
“…In 2017, Xie et al [35] designed a first roaming authentication scheme which takes the advantage of the chaotic maps for key agreement in ubiquitous network. Subsequently, in 2019, Ostad-Sharif et al [33] found that Xie et al [35] cannot resist the known sessionspecific information attack. In 2018, Lee et al [20] claimed that Chaudhry et al [19] is vulnerable to many attacks such as user forgery attacks and device theft attacks [37][38][39][40].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the computational time analysis, we account T h ≈ 0.0023ms, T mul ≈ 2.226ms, T fun ≈ 0.0046ms as reported in [33] and [34]. According to the Table 3 and Table 4, our protocol provides more security features with the addition of a small amount of computation.…”
Section: Performance Comparison and Efficiency Analysismentioning
confidence: 99%
“…However, when the number of users increases, it will occupy a lot of storage space of the service provider, which is not suitable for satellite with shortage of resources. In global mobility networks, [12] proposed a roaming authentication scheme based on the chaotic map-based discrete logarithm problem (CMBDLP). When a user and the foreign agent authenticate with each other, they need to transfer information four times with the participation of home agent, which increases the user's waiting time, and this does not meet the SIN low-latency requirement.…”
Section: Introductionmentioning
confidence: 99%